2013
DOI: 10.4103/1463-1741.116575
|View full text |Cite
|
Sign up to set email alerts
|

Distortion product otoacoustic emission level maps from normal and noise-damaged cochleae

Abstract: Distortion product otoacoustic emission (DPOAE) level mapping may be useful for detecting noise-induced hearing loss (NIHL) early. Employing DPOAE mapping effectively requires knowledge of the optimal mapping parameters to use for detecting noise-induced changes. The goal of this project was to show the map regions that differ most between normal and noise-damaged cochlea to determine the optimal mapping parameters for detecting NIHL. DPOAE level maps were generated for the 2f 1 -f 2 and the 2f 2 -f 1 DPOAEs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 5 publications
1
11
0
1
Order By: Relevance
“…The results of Mink's study on using the map of emission distortion levels of DPOAEs in Coclé damaged by noise and healthy Coclé showed that the DPOAEs range of group with NIHL is significantly weaker with P ≤ 0.01 compare to the healthy group. [25] According to the results of the present study and previous studies, it seems that DPOAE detects hearing loss caused by noise one phase earlier compare to PTA. However, future studies should try to provide more valid documents on the levels of DPOAE and controlling variables such as duration of exposition, smoking, and blood pressure levels.…”
Section: According Tosupporting
confidence: 82%
See 1 more Smart Citation
“…The results of Mink's study on using the map of emission distortion levels of DPOAEs in Coclé damaged by noise and healthy Coclé showed that the DPOAEs range of group with NIHL is significantly weaker with P ≤ 0.01 compare to the healthy group. [25] According to the results of the present study and previous studies, it seems that DPOAE detects hearing loss caused by noise one phase earlier compare to PTA. However, future studies should try to provide more valid documents on the levels of DPOAE and controlling variables such as duration of exposition, smoking, and blood pressure levels.…”
Section: According Tosupporting
confidence: 82%
“…[11,12,21] OAE is an objective test which can be more affordable compared to PTA due to its being cheap, act quickly and save time, not to need acoustic room, and sensitivity to hear losing. [13,[22][23][24][25] The study was conducted using PTA and OAE tests in two groups, i.e. control group including people exposed to industrial noise and without NIHL and experimental group including people with NIHL.…”
Section: Original Articlementioning
confidence: 99%
“…Effort was exerted to optimize distortion-product otoacoustic emission (DPOAE) for tracking noise-exposed subjects longitudinally. [ 41 ] Although the first observation in construction workers was promising in the aspect of the higher sensitivity of DPOAE (mainly at 4 kHz) in monitoring early signs of NIHL, a 10-year prospective study showed no advantage of this method over standard audiometry. [ 13 ] One of the limitations of translating the data is that significant individual otoacoustic emission (OAE) changes do not necessarily follow the same pattern as the group-averaged results.…”
Section: Noise-induced Hearing Lossmentioning
confidence: 99%
“…The DPOAE level reflects the function of the outer hair cells in the cochlea. 17 Our results indicated that there outer hair cell damage occurred early after radiotherapy. The hair cell damage after radiotherapy resulted from several causes.…”
Section: Discussionmentioning
confidence: 51%
“…We found that the DPOAE levels decreased after irradiation. The DPOAE level reflects the function of the outer hair cells in the cochlea . Our results indicated that there outer hair cell damage occurred early after radiotherapy.…”
Section: Discussionmentioning
confidence: 65%